A clinical study to evaluate the role of Madhumehari Vati in the management of Madhumeha type 2 diabetes - Sharma, Sachin Kumar; Dave, Alankruta R.; Vasishth, Brijbala; Sharma, Vasundhara (International Journal of Advances in Medicine, 2021)
Background: Type 2 Diabetes is a major, non-communicable disease with increasing prevalence at the global level. Type 2 diabetes is a metabolic disorder which can be correlated with Madhumeha. Madhumeha is Tridoshaj in origin with predominance of Vata and Kapha. Type 2 diabetes results when the body produces insufficient insulin or the body cannot use the insulin it produces. Most of the contents of Madhumehari Vati are having Katu (pungent), Tikta (bitter), Kashaya (astringent) Rasa (taste), Laghu (light), Ruksha (rough) Guna (properties), Katu (pungent) Vipaka (taste after digestion), Ushna (hot) Virya (potency), Deepana, Pachana Kapha-Pitta Shamaka properties and hypoglycaemic,antidiabetic activity,Hepatoprotective, hypolipidemic and antioxidant activities which are essential in the management of Madhumeha (type 2 diabetes). So, this study was taken up to evaluate the effectiveness of Madhumehari Vati in the management of Madhumeha (type 2 Diabetes). Aim of the study was to evaluate the efficacy of Madhumehari Vati in the management of Madhumeha w.s.r type 2 diabetes. Methods: Total 31 patients were selected from OPD of Kayachikitsa, department, I. T. R. A., Jamnagar. In this study Madhumehari Vati was given in dose of one tablet (1000 mg each) three times in a day with plain water before meal. Results: After the course of therapy for 8 weeks, statistically highly significant improvement was found in subjective parameters like Pindikodwestana (calf muscles cramps), Guru Gatrata (heaviness of body), Supti (numbness), Karapada Daha (burning sensation in palm and soles), Prabhutamutrata (polyuria), Atipipasa (polydipsia) whereas Shithila Angata (flaccidity of body parts), Swedadhikya (excessive sweating), Kshudha Adhikya (polyphasia) and Nidra Adhikya (excessive sleep) remained statistically significant (p<0.05). In objective parameters statistically highly, significant improvement was found in post prandial blood glucose whereas statistically significant improvement was found fasting blood glucose and HbA1C. Conclusions: Madhumehari Vati is effective in the management of Madhumeha (type 2 diabetes). No ADR (adverse drug reaction) was reported during the study.